Estimating HIV-1 Transmission Routes for Patients With Unknown Risk Histories by Viral Sequence Phylogenetic Analyses. (1st October 2015) - Wei, Min; Xing, Hui; Feng, Yi; Hsi, Jenny H.; Liu, Pengtao; Shao, Yiming
Abstract : Objective: To estimate routes of transmission among HIV-infected persons with unknown-risk histories in China. Design/Method: All newly reported cases of HIV infection between year 1985 and 2009 were obtained from the National Databank of Chinese Center for Disease Control and Prevention (China CDC). A large number of unknown-risk HIV-positive samples were found. To estimate the transmission routes, HIV gag sequences were amplified by reverse transcription polymerase chain reaction and phylogenetically analyzed. The cases with unknown-risk history were compared with those with known-risk histories from the same local region and time period. A statistical model was developed to predict the transmission routes and was validated on known-risk samples, before testing 324 unknown-risk samples collected from 1996 to 2006. Results: Newly reported cases of HIV infection in China increased steadily between 1985 and 2009, from just a handful of cases to 30, 340 in 2009. Injecting drug use (IDU) was the dominant route of transmission among reported cases in the early years and decreased from 83.4% in 1985–2001 to 28.2% in 2009. Conversely, sexual transmission increased from 6.9% in 1985–2001 to 60.9% in 2009. Among the 324 unknown-risk HIV sequences collected from 1996 to 2006, our model identified 100 samples most likely transmitted by blood, 114 by IDU, and 110 by sexual transmission. Our validation samples showed that our model has 90.8%, 94.8%, and 69.6% sensitivity and 87.3%, 87.5%, and 85.5% specificity, for blood, IDU, and sexual transmission, respectively. Conclusions: We developed a model to estimate transmission route of unknown-risk HIV-positive samples and found that these unknown-risk patients could be transmitted by blood, IDU, or sex. Abstract : Supplemental Digital Content is Available in the Text.